2023
DOI: 10.1093/qopen/qoad017
|View full text |Cite
|
Sign up to set email alerts
|

The impact of information and communication technology on the technical efficiency of smallholder vegetable farms in Shandong of China

Abstract: Farmers have started to adopt Information and Communication Technology (ICT), which has considerable potential to impact farm performance. This study uses data from a 2018 survey of 763 vegetable smallholder farms in China to estimate the impact of ICT on technical efficiency (TE). We adopt propensity score matching to create a balanced sample of ICT users and non-users, and a stochastic frontier model with sample selection correction to compare the two groups’ TE. After accounting for self-selection bias from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Shandong Province has a very wide area of cropland, but is affected by the topography, and some of the cropland is highly fragmented and spatially distributed, facing serious mixed image meta-problems even on the basis of a 10 m resolution. Furthermore, it is an agricultural area dominated by smallholder farming, which is a strong flexibility in the family-based farming practices and an orientation towards economic return [67,68]. Especially in hilly areas, intercropping is very common.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Shandong Province has a very wide area of cropland, but is affected by the topography, and some of the cropland is highly fragmented and spatially distributed, facing serious mixed image meta-problems even on the basis of a 10 m resolution. Furthermore, it is an agricultural area dominated by smallholder farming, which is a strong flexibility in the family-based farming practices and an orientation towards economic return [67,68]. Especially in hilly areas, intercropping is very common.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Crop and vegetable farmers in less developed countries face challenges such as a lack of education and experience, restricted access to inputs, and inferior agricultural extension services. By facilitating direct, fast, and global information and idea exchange between farmers and experts and addressing these issues (Hobbs, 1996;Bozoğlu and Ceyhan, 2007;Aker, 2008;Schmidt and Wagner, 2019;Quintana-García et al, 2021;Kang et al, 2023), ICT enhances the transmission of information. Producers may also gain greater access to advice and instruction from reliable professionals.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Jin et al (2023) highlighted that while productivity advancements impact natural ecology due to population growth, the focus should be on adopting low-carbon and science-based agricultural practices rather than halting productivity. Research conducted in Shandong province by Kang et al (2023) shed light on the impact of ICT utilization on the growth, performance, and delivery of vegetable farms. Additionally, Li et al (2023) suggested that utilizing IT might help narrow the income gap between rural and urban areas.…”
Section: Introductionmentioning
confidence: 99%